Localization of the Bochner-Riesz means in the Nikol'skii classes - Grona, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We investigate the conditions for the localization of the Bochner-Riesz means in the Nikol'skii classes $u_p^α$ for $p \in [1, 2]$.